The Narrative Cores of Neighbourhood Reputation as Revealed by Temporal Discourses - Heino, Hanna; Honkaniemi, Tuomas; Luoto, Ilkka (John Wiley & Sons, 2024)
Neighbourhood reputation is an elusive but much discussed and studied concept that greatly influences people's perceptions of and attitudes towards the residential areas of a city. The temporality related to neighbourhood reputation is a less studied topic. The emergence of a place-based reputation is a complex social, spatial, temporal, and cultural process that is affected by the neighbourhood's residents and visitors, local and social media, and non-residents who are knowledgeable about the area. We based our study of reputation on interviews with focus groups, city officials, and politicians. According to the interview data, neighbourhood reputation is articulated through four temporal discourses: the past, presentation, representation, and the future. Ultimately, underlying these four temporal discourses we found causes for neighbourhood reputation and stigmatisation that we named as narrative cores.
Keywords: Temporality; Narrative core; Focus groups/Expert interviews; Finland; reputation; neighbourhood (properties); fi=Aluetiede|en=Regional Studies|